A Pilot Clinical Study Assessing Treatment of Canine Hip Dysplasia Using Autologous Protein Solution - Franklin, Samuel P. (Frontiers in Veterinary Science, 2019)
Five dogs with bilateral hip dysplasia and without osteoarthritis of other joints were enrolled in this pilot study. Objective kinetic data using a pressure sensitive mat and owner assessments using the canine brief pain inventory (CBPI) and Liverpool Osteoarthritis for Dogs (LOAD) questionnaires were obtained prior to treatment. Enrolled dogs were treated in one hip with autologous protein solution (APS) and the contralateral hip was injected with an equal volume of saline. The hip to be treated was selected using a random number generator. At exactly 28 days following treatment dogs were re-assessed using the pressure sensitive mat and the CBPI and LOAD questionnaires. No dogs were treated with any other medications or supplements throughout the study period. Assessment of the total pressure index collected using the pressure sensitive mat showed that the hips treated with APS improved significantly more than hips treated with saline (p=0.0005) and that the hips treated with APS bore significantly more weight than the hips treated with saline at day 28 (p < 0.05). Statistically significant improvement was noted by owners in “pain” and “function” as assessed by the CBPI as well “mobility at exercise” using the LOAD questionnaire. This pilot study provided proof of principle that APS is beneficial in treating pain and lameness in dogs affected by coxofemoral osteoarthritis.